Cupcake cousins - Hannigan, Kate (Disney * Hyperion Books, 2014)
During a family vacation at Lake Michigan, nine-year-old cousins Willow and Delia, desperate to avoid being flower girls in their aunt's wedding, try to demonstrate that they would do better as chefs for the reception.